Employee Environmental Awareness Pada Keberlanjutan UMKM Industri Pariwisata Kota Pari Pantai Cermin - Ario, Firman; Harianto; Harahap, Ramadhan; Pratama, Deny (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2024)
The tourism industry holds significant potential for supporting local economic growth, particularly in tourist areas like Kota Pari Pantai Cermin, where SMEs play a crucial role. However, the rapid growth of this industry brings challenges related to environmental and sustainability issues. Green marketing has become a key strategy to meet changing consumer preferences for environmentally friendly products. Enhancing employee environmental awareness is also vital to improving sustainability in this sector. This study aims to analyze the impact of green marketing and employee environmental awareness on the sustainability of tourism SMEs in Kota Pari Pantai Cermin, utilizing an associative method with 100 respondents from tourism SMEs that developed between 2022 and 2023. The results show that employee environmental awareness, SME competitiveness, and tourism industry development significantly influence SME sustainability. Recommendations from this study include increased environmental training for employees and support for environmental initiatives from SME owners. This research is expected to provide insights for sustainable policy development that supports both environmental and economic sustainability at the local level.